The Legal Character of Provincial Agreements with Foreign Governments - van Ert, Gibran (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 2001)
The object of this article is to consider the legal character of provincial agreements with foreign governments and the constitutional authority of provincial governments to make them. The matter is controversial ; Quebec has long maintained that provincial governments are competent to conclude treaties in areas of provincial jurisdiction, while the federal government asserts that it alone can conclude binding treaties. The argument of this essay is that the traditional arguments made for and against provincial competence to conclude treaties are equally unsatisfying. The best answer comes from a close analysis of the unwritten constitution from which the treaty power arises. Such analysis suggests that the otherwise credible argument, that the treaty-making power has devolved uniquely upon the federal government by a crystallization of constitutional usage into constitutional law, is blocked by Quebec's persistent objections over nearly forty years. Thus, the legal question of capacity to conclude treaties remains unresolved and indeed irresolvable without political dialogue. Finally, the article suggests that even if provinces do not have the power to make binding treaties, courts may nevertheless use provincial agreements with foreign governments, in the proper case, as a guide to the construction of legislation.